The efficacy of a whole foods, plant-based dietary lifestyle intervention for the treatment of peripheral neuropathic pain in leprosy: a randomized control trial protocol - Klowak, Michael; Boggild, Andrea K. (Frontiers in Nutrition, 2023)
Introduction Despite effective treatment of leprosy via WHO-approved multi-drug therapy (MDT), patients still suffer from debilitating neuropathic sequelae, including peripheral neuropathic pain (PNP), and continue to develop intercurrent etiologies (such as diabetes), and progressive existing neuropathy over time. Strategies seeking to improve physiological and metabolic wellness, including those that reduce systemic inflammation and enhance immune responsiveness to neurotoxic factors may influence underlying neuropathic etiologies. A whole food plant-based diet (WFPBD) has been shown to be effective in the management of neuropathic pain due to diabetes, limiting severity and relevant symptomology. Diabetes remains a significant sequela of leprosy, as up to 50% of patients in reaction requiring corticosteroids, may develop a biochemical diabetes. As nutritional interventions may modulate both leprosy and diabetes, a specific exploration of these relationships remains relevant. Objectives (1) To demonstrate the effect of a WFPBD lifestyle intervention, on neuropathic pain variables in leprosy; and (2) To contextualize the significance of diet in the treatment of chronic sequelae in leprosy by evaluating tolerability and side effect profile. Methods A prospective, randomized, controlled, single-blind, multicentre interventional trial is described. Weekly one-hour dietary counseling sessions promoting a WFPBD emphasizing vegetables, fruits, whole-grains, nuts, and legumes, omitting animal products, and limiting fat intake over a six-month duration will be implemented. Participants will be 70 age and sex-matched individuals experiencing active or treated “cured” leprosy and PNP, randomized to either intervention or control groups. Primary outcome measures include efficacy via visual analog scale, subjective questionnaire and objective quantitative sensory testing, as well as safety, tolerability, and harms of a WFPBD on PNP in leprosy. This study will be initiated after Research Ethics Board (REB) approval at all participating sites, and in advance of study initiation, the trial will be registered at ClinicalTrials.gov. Expected impact It is hypothesized that WFPBDs will mitigate progression and severity of PNP and potentially reduce the adverse events related to standard corticosteroid treatment of leprosy reactions, thereby reducing disease severity. By examining the effects of WFPBDs on PNP in leprosy, we hope to illuminate data that will lead to the enhanced therapeutic management of this neglected tropical disease.